FINANCIAL SUSTAINABILITY: ASSESSING THE INFLUENCE OF RISK MANAGEMENT ON SUSTAINABILITY REPORTING AND CORPORATE FINANCIAL PERFORMANCE - Alfistia Maradidya; Sri Anom Amongjati (Jurnal Penelitian Manajemen Terapan (PENATARAN), 2025)
This study aims to examine the influence of risk management on sustainability reporting and financial performance of mining sector companies in Indonesia. A quantitative approach was employed, using secondary data from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange during the period 2020–2022. Data analysis was conducted using multiple linear regression and Sobel mediation tests to assess the role of sustainability reporting as a mediating variable. The findings indicate that risk management has a positive and significant effect on the quality of sustainability reporting and directly influences financial performance. Furthermore, sustainability reporting partially mediates the relationship between risk management and corporate financial performance. These results highlight that integrating risk management with sustainability reporting strategies can strengthen stakeholder trust, improve performance, and support long-term financial sustainability.